Rebuilding the Missing Part—A Review on Photoreceptor Transplantation - Santos-Ferreira, Tiago F.; Borsch, Oliver; Ader, Marius (Frontiers in Systems Neuroscience, 2017)
Vision represents one of the main senses for humans to interact with their environment. Our sight relies on the presence of fully functional light sensitive cells – rod and cone photoreceptors - allowing us to see under dim (rods) and bright (cones) light conditions. Photoreceptor degeneration is one of the major causes for vision impairment in industrialized countries and it is highly predominant in populations above the age of 50. Thus, with the continuous increase in life expectancy it will make retinal degeneration reach an epidemic proportion. To date, there is no cure established for photoreceptor loss, but several therapeutic approaches, spanning from neuroprotection, pharmacological drugs, gene therapy, retinal prosthesis and cell (RPE or photoreceptor) transplantation, have been developed over the last decade with some already introduced in clinical trials. In this review, we focus on current developments in photoreceptor transplantation strategies, its major breakthroughs, current limitations and the next challenges to translate such cell-based approaches towards clinical application.